Chicken soup for the soul. Teens talk middle school : 101 stories of life love, and learning for youner teens. - Canfield, Jack; Hansen, Mark Victor; Clapps, Madeline; Howlett, Valerie (Estados Unidos : Health communications, 2008)
"The first day. The first kiss. The first time you got ditched by a friend because you weren't cool enough. The first time you were given real responsibilities. The first moment you realized you were growing up, changing, and becoming who you really are. These are the things that middle school is all you, and trust us- we know middle school." (Copiado del prefacio).
Foreword. Part 1. True friends and new friends. Part 2. Mean girls... and boys. Part 3. Embarrassing moments. Part 4. Bully payback. Part 5. Finding your passion. Part 6. In like, in love, and just not into you. Part 7. Being happy with yourself. Part 8. Tough times. Part 9. That's my family. Part 10. The people who are there for us. Part 11. Doing what´s right.